Introduzione al volume degli Atti. Territori, senso comune e intellettuali: il racconto di un’esperienza politica - Perra, Sabrina; Manduchi, Patrizia (International Gramsci Journal, 2023)
This is the Abstract of the Introduction to the volume of the Proceedings of the international conference Gramsci nel mondo di oggi published in the IGJ issue 16, summer 2022.